Spatial memory in Huntington's disease: A comparative review of human and animal data. (March 2019) - Glikmann-Johnston, Yifat; Fink, Kyle D.; Deng, Peter; Torrest, Audrey; Stout, Julie C.
Highlights: Preclinical testing in Huntington's disease (HD) animal models inform human trials. Cognitive testing is misaligned between preclinical and clinical trials. We show findings of spatial memory impairments in both human HD and mouse models. Spatial memory impairments are linked to HD neuropathology. Spatial memory has strong potential to bridge the translational gap between species. Abstract: To improve the translational predictability of treatment strategies for Huntington's disease (HD), sensitive and analogous cognitive outcomes are needed across HD animal models and humans. Spatial memory measures are promising candidates because they are based on 'visual' or 'non-verbal' cognition, and are commonly tested in both animals and humans. Here, we consider the suitability of spatial memory for strengthening translational links between animals and humans in HD research and clinical trials. We describe findings of spatial memory impairments in human HD and mouse models, including which aspects of spatial memory are most affected and at which time points in disease progression. We also describe the neural systems that underlie spatial memory and link spatial memory impairments to HD neuropathology, focussing on striatal and hippocampal systems. We provide a critical analysis of the literature in terms of the suitability of spatial memory for bridging the translational gap between species. Finally, we discuss possible neural mechanisms that might explain the spatial memory impairments seen in HD, and their relevance to potential treatments.